Special Circumstances - Teleki, Marianne; Salgado, Hector (Tunnel Productions, 2006)
Verzio FF Submission At 16, Hector Salgado was arrested and tortured by Pinochet's forces. By 20, Hector was without a country, living in exile in the US, the very place whose devastating foreign policies in Chile caused the death and torture of 1,000s of Chileans. The documentary follows Hector as he returns to Chile almost 30 years later, camera in hand, to confront the perpetrators and his former captors looking for answers and justice. In the process 'Special Circumstances' takes an unflinching look at US foreign policy in Latin America in the '70s and the legacy of Pinochet.